1996
DOI: 10.1128/jb.178.18.5499-5507.1996
|View full text |Cite
|
Sign up to set email alerts
|

Siderophore-mediated iron uptake in Alcaligenes eutrophus CH34 and identification of aleB encoding the ferric iron-alcaligin E receptor

Abstract: Siderophore production in response to iron limitation was observed in Alcaligenes eutrophus CH34, and the corresponding siderophore was named alcaligin E. Alcaligin E was characterized as a phenolate-type siderophore containing neither catecholate nor hydroxamate groups. Alcaligin E promoted the growth of siderophore-deficient A. eutrophus mutants under iron-restricted conditions and promoted 59 Fe uptake by ironlimited cells. However, the growth of the Sid ؊ mutant AE1152, which was obtained from CH34 by Tn5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 59 publications
1
38
0
1
Order By: Relevance
“…BLASTP analysis at the P. aeruginosa Genome Project database revealed that PA4675 displays 46 % identity to IutA. An additional putative TonB-dependent receptor, PA1365, displaying 29 % identity to IutA was also identified, although this receptor displays over 50 % identity with the alcaligin E receptor, AleB, from Ralstonia metallidurans (Gilis et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…BLASTP analysis at the P. aeruginosa Genome Project database revealed that PA4675 displays 46 % identity to IutA. An additional putative TonB-dependent receptor, PA1365, displaying 29 % identity to IutA was also identified, although this receptor displays over 50 % identity with the alcaligin E receptor, AleB, from Ralstonia metallidurans (Gilis et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…For a number of reasons, we strongly believe that this CAS-reactive substance represents a bona fide siderophore. First, the CAS assay has reliably identified and characterized a range of siderophores encompassing the iron chelators of over 20 bacterial genera (2,3,5,12,18,20,21,27,33,36,37,38,47,48,51,58,66,68,74,80,82,85,98). Second, the presence of CAS-reactive material correlated with enhanced aerobic growth in an iron-depleted defined medium (68).…”
Section: Discussionmentioning
confidence: 99%
“…This list has grown appreciably in recent years, largely due to the availability of the CAS assay. There are a number of other bacterial siderophores that, like legiobactin, do not possess the classic catecholate or hydroxamate structure and thus were or would have been overlooked by the Arnow and Csáky assays (12,15,18,33,37,61,68,85,94). In some ways, it is not surprising that L. pneumophila produces a siderophore.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 depicts the possible locations of the products of these genes in cells, as predicted from the locations of their homologues. Sll1406, Sll1409, Slr1490, and Sll1206 are homologous to FhuA of E. coli (7) and IutA of Alcaligenes eutrophus (10), which are located in the outer membrane. Sll1202, Slr1491, Slr1492, and Slr1319 showed similarities with FhuD and FecB of E. coli (7,22).…”
Section: Location Of Gene Products and Genes Inactivated In The Mutantsmentioning
confidence: 99%